Glycine-functionalized Ti3C2Tx MXene with improved material properties for concurrent Sn2+ oxidation mitigation and defect passivation in efficient tin halide perovskite solar cells - Mohammed, Aseel j.; Dizayee, Wala; Marhoon, Ismail Ibrahim; Mohammed, Mohammed Ahmed; Zorah, Mohammed; Al-Husseini, Zainab Shaker Matar; Abdulnabi, Mohamed Shabbir; Abdulkareem-Alsultan, G.; Nassar, Maadh Fawzi (Elsevier, 2026)
Lead-free tin halide perovskites constitute a nontoxic alternative to lead-based solar absorbers, but their development is stifled by low performance and material instability, attributed primarily to Sn2+ oxidation, high levels of defects, and slow charge transfer. We demonstrate glycine-functionalized Ti3C2Tx MXene (MXG) as a multifunctional additive in FASnI3 perovskite films. The amino groups on MXG have a two-fold role in that they chemically passivate the under-coordinated Sn sites and iodine vacancies, while at the same time providing moderate reductants to suppress Sn2+ oxidation. Aside from passivation, the MXene with layered conductive properties also acts as a favorable template for perovskite crystallization, allowing the vertical grain orientation for better light absorption into the absorber layer, improveing interfacial connection between layers and charge carrier transfer/extraction. For the MXG devices, better film quality and reduced trap state density and carrier lifetime with enhanced energy level alignment were observed. The champion MXG/FASnI3 device shows a power conversion efficiency of 15.82 % with improved stability (maintaining over 94 % of its initial efficiency after 1000 h). This investigation highlights the dual electrical and structural benefits of MXene engineering toward achieving earth-abundant, efficient, stable, and scalable Sn perovskite PVs.